Ni-samaria-doped ceria (Ni-SDC) anode-supported solid oxide fuel cell (SOFC) operating with CO. (6th April 2017) - Ideris, Asmida; Croiset, Eric; Pritzker, Mark
Abstract: The performance of nickel-samaria-doped ceria (Ni-SDC) anode-supported cell with CO-CO2 feed was evaluated. The aim of this work is to examine carbon formation on the Ni-SDC anode when feeding with CO under conditions when carbon deposition is thermodynamically favoured. Electrochemical tests were conducted at intermediate temperatures (550–700 °C) using 20 and 40% CO concentrations. Cell operating with 40% CO at 600–700 °C provided maximum power densities of 239–270 mW cm −2, 1.5 times smaller than that achieved with humidified H2 . Much lower maximum power densities were attained with 20% CO (50–88 mW cm −2 ). Some degradation was observed during the 6 h galvanostatic operation at 0.1 A cm −2 with 40% CO fuel at 550 °C which is believed due to the accumulation of carbon at the anode. The degradation in cell potential occurred at a rate of 4.5 mV h −1, but it did not lead to cell collapse. EDX mapping at the cross-section of the anode revealed that carbon formed in the Ni-SDC cell was primarily deposited in the anode section close to the fuel entry point. Carbon was not detected at the electrolyte-anode interface and the middle of the anode, allowing the cell to continue operation with CO fuel without a catastrophic failure. Highlights: The performance of nickel-samaria-doped ceria (Ni-SDC) anode-supported cell was evaluated under CO-CO2 feed. Some degradation was observed during the 6 h galvanostatic operation with 40% CO, but did not lead to cell collapse. Carbon formed in the Ni-SDC cell was only found at the anode section close to the fuel entry point.